Characterisation of Cold Bituminous Emulsion Mixtures Using Microwave Heating Process. Issue 1 (August 2021) - Al-Busaltan, Shakir; Nageim, Hassan Al; Dulaimi, Anmar; Shanbara, Hayder Kamil; Kadhim, Mustafa Amoori; Al-Kafaji, Muna
Abstract: A previous study conducted by the authors proved that the inferiority of the mechanical properties of Cold Bituminous Emulsion Mixtures (CBEMs) could be overcome by incorporating a waste or by-product material, namely Paper Sludge Ash (PSA). The new CBEMs have demonstrated comparative mechanical and durability properties compared to conventional Hot Mix Asphalt (HMA). Furthermore, the new CBEMs have less impact on the economy, environment, and safety. However, the air void content of the new CBEMs is still high – to a stage unacceptable by pavement engineers. Thus, this study introduces a treatment method to reduce the air void without affecting the improvement achieved in mechanical properties and other environmental and economic issues. This study presents microwave energy treatment as a unique post-mix treatment method to overcome high air void content in CBEMs. Test results showed that microwave energy improves the stiffness modulus and air void content. However, new post-mix microwave treatment CBEMs still have comparative mechanical, volumetric, economic, and environmental characteristics to HMA.